Kuat Tekan Bebas Tanah Lempung Distabilisasi Pasir dan Semen untuk Perkerasan Jalan Raya - Anwar Muda (Media Ilmiah Teknik Sipil, 2017)
This study aims to determine the compressive strength of clay and sand stabilized clay soil for pavement. The results showed that the sand stabilization was 12% with 2% cement, the UCS value rose to 0.49 kg / cm2 from the initial condition 0.41 kg / cm2. Then, the addition of cement 4%, the UCS value also increased by 4.44 kg / cm2. On the addition of cement by 6%, the UCS value increased to 5.29 kg / cm2 and the addition of cement by 8%, the UCS value rose to 7.33 kg / cm2 and the addition of cement 10%, the UCS value increased to 9.06 kg / cm2. So, with the addition of sand by 12% and optimum cement 8%, it meets the technical requirements of the lower foundation layer of the road because the UCS value is 7.33 kg / cm2> 6 kg / cm2.